SISTEM INFORMASI PENJUALAN PADA KEDAI KOPI NIKMAT: SYSTEM, INFORMATION, SALES, VISUAL BASIC 6.0 - Indra, Sum (LP2M STMIK Nurdin Hamzah Jambi, 2019)
Nikmat Coffee Shop has many coffee varieties such as Mandailing Civet Coffee, Toraja Coffee, Java Coffee, and many other varieties of coffee. This shop offers a variety of drinks and scrumptious foods which are also an attraction for visitors who come. The menu needed is like an oxtail soup complete with rice and vegetables, besides that there is also a food menu such as grilled chicken, fried rice and various other drinks. Coffee Shop Favor Sales transactions are still manuals or still use books in registration of transaction results. The calculation of sales transaction data is not accurate and not well recorded, so losses often occur which eventually become large losses. As time goes by, this manual recording will make more data more difficult to manage. One of the facilities that can help owners in managing sales data recording activities is by making a sales information system for the Delicious Coffee Shop. This sales information system is expected to help process coffee shop data so that it can improve and improve sales calculations, manage reports and improve the performance of the delicious coffee shop for customers using a new system that is easy, fast and produces accurate information.